2022
DOI: 10.1590/1413-81232022276.11842021
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behavior and health-related quality of life in adolescents

Abstract: Health-related quality of life (HRQoL) represents the perception of each person about different aspects of their lives in the health context (physical, psychological, social environment and interpersonal relationships). Among adolescents, HRQoL can change considering habits adopted in this phase of life. This study analyzed the association between time used on different sedentary behaviors (SB) and HRQoL in adolescents. This is a cross-sectional epidemiological study with adolescents between 10 - 15 years of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
6
0
2
Order By: Relevance
“…Prolonged periods of time engaged in screen activities (e.g., watching TV, using computers, smartphones, and tablets) also contribute to SB [ 7 , 8 , 9 ]. A previous study indicated that approximately 71% of adolescents from Brazil demonstrated excessive screen time [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged periods of time engaged in screen activities (e.g., watching TV, using computers, smartphones, and tablets) also contribute to SB [ 7 , 8 , 9 ]. A previous study indicated that approximately 71% of adolescents from Brazil demonstrated excessive screen time [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…), most of the studies assessed SB only by TV time [ 7 ]. Excessive screen time may negatively impact health-related quality of life (HRQoL) [ 8 , 10 ]. Adults and adolescents that spent long stretches of time on screen devices presented unfavorable dietary habits, as well as impaired physical and mental health (e.g., anxiety, headaches, perceived stress) and decreased HRQoL [ 9 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embora se reconheça que a tecnologia faz parte do social e anular seu uso é uma pretensão que parece estar na esfera do impossível, é preciso perceber que a problemática está na forma que é utilizada e não na tecnologia propriamente dita. Assim, destaca-se a relevância da presença, da responsabilização e da mediação dos pais e responsáveis no controle do uso de telas, visto que a criança ainda não possui a capacidade de decidir sobre suas atitudes e sobre o que é melhor para si (Lucena et al, 2022).…”
Section: -Uso De Telas E a Preocupação/controle Dos Paisunclassified

Estudos Multidisciplinares Sobre Saúde Da Criança E Do Adolescente

RIBEIRO DE SOUSA,
MARQUES DAS CHAGAS,
EDUARDO DA SILVA BARBOSA
et al. 2023
“…Lucena et al [ 36 ] found a positive relationship between “SS and peer group” and ST. The measurement of the social variable was with the KIDSCREEN-27 instrument, which asks about SS but in a generalized way, with no specific item on PA.…”
Section: Introductionmentioning
confidence: 99%